Strategic Management in Developing Leadership Character in the OSIS Program at SMPN 11 Kota Sungai Penuh - Miftahul Jannah; Mohamad Muspawi (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to analyze the application of strategic management in shaping the leadership character of students through the OSIS program at SMPN 11 Kota Sungai Penuh. Employing a qualitative approach with a descriptive research method, the study provides a detailed examination of social events related to OSIS management. Data were collected through field methods, including direct observation, in-depth interviews with school leaders, OSIS supervisors, and student members, as well as documentation of OSIS activities. Data analysis involved interactive and continuous techniques, including data condensation, data presentation, and conclusion drawing, supported by triangulation to ensure data validity, credibility, and dependability.The findings reveal that (1) Strategic Planning includes structured steps such as setting targets, formulating objectives, and developing strategies and sub-plans to ensure the program aligns with the school's vision and mission; (2) Strategic Organizing involves grouping activity components, assigning tasks, and delegating authority to ensure systematic and directed program execution; (3) Strategic Implementation is carried out through communication, motivation, and supervision to foster effective coordination and encourage student participation; and (4) Strategic Supervision is conducted via periodic evaluations to assess and improve program effectiveness, while also fostering innovation and creativity. This structured approach to strategic management significantly contributes to the sustainable development of student leadership character.